Adjuvant activity of ethanol extract of Hippophae rhamnoides leaves with inactivated rabies virus antigen - D. Singh; B. Jayashankar; K. P. Mishra; H. Tanwar; S. N. Madhusudana; A. Y. Belludi; R. Tulsawani; S. B. Singh; L. Ganju (Taylor & Francis Group, 2018)
Context: Hippophae rhamnoides L. (Elaeagnaceae), commonly known as seabuckthorn (SBT), is known for its medicinal and nutritional properties. Objective: Evaluation of in vivo adjuvant activity of SBT leaf extract (SBTE) with inactivated rabies virus antigen (Rb). Materials and methods: Swiss albino mice were immunized with aqueous-alcoholic SBTE (100 mg/kg body weight) or algel (aluminium hydroxide gel) with or without Rb (5% v/v). After priming, booster was administered on day 14. Rabies virus neutralizing antibody (RVNA) titers were estimated by rapid fluorescent focus inhibition test in sera samples collected on days 7, 14, 21, 28 and 35. Effect of adjuvant administration on cytotoxic T lymphocytes (CTLs), memory T cells, plasma and CD11c+ cells was studied by flow cytometry. In vitro hemolysis was assayed in human RBC. Results: RVNA titers were significantly enhanced (p < 0.05) after booster administration in mice immunized with SBTE + Rb as compared to the controls. In combination, SBTE, algel and Rb, enhanced the RVNA titers. CTLs significantly increased (p < 0.05) in SBTE + Rb immunized mice. Memory T cells and plasma cells were 27.9 and 15.9%, respectively, in SBTE + Rb immunized mice as compared to that of 20.3 and 11.3%, respectively, in Rb immunized group. SBTE + Rb enhanced peritoneal CD11c+ cells (25.8%) as compared to 9.4% cells in Rb immunized mice, showed 3.2-fold increment in LPS induced IL-1β. No RBC hemolysis was observed with SBTE. Conclusions: This study demonstrates the potential adjuvant activity of SBTE with Rb by increasing RVNA titers and CTL response.